Determinasi Strain Aedes aegypti (Linn.) yang Rentan Homozigot dengan Metode Seleksi Indukan Tunggal - Isfanda Isfanda; Upik Kesumawati Hadi; Susi Soviana (ASPIRATOR - Journal of Vector-borne Disease Studies, 2017)
Aedes aegypti is a type of mosquito that can carry dengue virus, yellow fever and chikunguya. Thespread of this mosquito is very broad, covering almost all tropical regions worldwide. This study aims todetermine the vulnerability status of homozygous Ae. aegypti. Sample of Ae. aegypti is mosquito strain fromHealth Entomology Laboratory Bogor Institute of Agriculture and at random sampling. Ae. aegypti eggswhich comes from the breeders hatched separately. Insecticide‐treated paper (impregnated paper)malathion, bendiokarb and deltamethrin are use for insecticides testing using WHO test kit. The analysisshowed that the mosquito Ae. aegypti tested with a single sib‐selection method and were exposed to theinsecticide malathion, propoksur, and showed an increasing trend sipermetrin vulnerability homozygous ateach generation. As for the fourth generation (F4) has not shown changes into a strain that is homozygoussusceptible to three types of insecticides. The formation of homozygous susceptible strains take over fivegenerations.